Concept of Non-Discrimination Letter of Inheritance Rights Based on Positive Law in Indonesia - Bunawan, Petra; Syafriani, Ilma (International Journal of Latin Notary, 2024)
The certificate of heirs serves to show who is entitled to the inheritance left by someone who has died (heir) which forms the basis for the department of inheritance each over who's entitled and/or how many stocks are entitled to be owned by using the heirs. There are 3 (3) officers for Making heir certificates, specifically Notary, Probate court and Lurah/Village heads and showed by means of the sub-district head. The question why the certificate of heirs is not made through only one reputable has its very own ancient historical past..The criminal arrangements that were in impact at that time in Indonesia did no longer offer felony truth, and at this country followed elegance discrimination. an appropriate is as a country that were unbiased from Dutch colonialism, which have to have abolished the type of the populace race in Indonesia. The classification of the populace race isn't according with Pancasila and the charter, because it includes the precept of discrimination and is a legacy of the nation that used to colonize Indonesia. At present Citizenship law variety 12 of 2006 which turned into surpassed on June 21, 2006 which in principle simplest acknowledges Indonesian citizens and foreign residents and now not mentions population type. in addition, law variety 23 of 2006 as amended by law wide variety 24 of 2013 regarding population administration has additionally abolished it. The non-discrimination precept is also said via regulation quantity 40 of 2008 regarding the removal of racial and ethnic discrimination. This law explicitly orders all elements of country management to do away with all forms of discrimination in opposition to race and ethnicity. consequently, non-discrimination principle need to be applied in inheritance certificates and the legal authentic in making the assertion of inheritance rights, by means of the officials who has the authority to put in writing it. Prioritizing the principle of non-discrimination is a need to.